The effect of cobalt60 radiation on squamous cell carcinomas of the nasal planum of the domestic cat - Crewe, Georgina (My University, 2010)
Squamous cell carcinomas (SCC) are caused by high levels of UVB (B fraction of the ultra violet ray) radiation on susceptible animal tissue. Factors that influence the ultra violet radiation (UV) level in different parts of the world are altitude, intensity and duration of sunlight, and thickness of the ozone layer. South Africa’s UV radiation levels are amongst the highest recorded in the world. The UVB energy enters the squamous cell and damages the DNA, which results in the uncontrolled proliferation of the squamous cells. Ultimately this proliferation of the squamous cells leads to the formation of a squamous cell carcinoma. The normal histology of the well-ordered squamous cell tissue changes from its regular pattern to one of disintegration as the carcinoma grows at the expense of the normal tissue. This clinical study examines the results of 75 feline patients with solar-induced SCC of the nasal planum treated with Cobalt 60 radiation. The cats were grouped clinically according to the severity of the SCC from 1-4, least to worst. The cats were sedated and their nasal planums irradiated on a recognised veterinary fractionated protocol of Monday/Wednesday/Friday. The clinical response was judged by the visual reduction in size and the diminishing aggressiveness of the tumour. This response determined the radiation dose and the number of treatments. The cats, age, sex, clinical appearance, number of treatments, radiation dose and survival period were recorded. A photographic record was kept of the patient’s progress before, during, and after treatment and the cats’ subsequent period of monitoring. Environmental compliance by the owners with respect to limiting exposure to solar radiation was also recorded. The cats were monitored for two years after the initial radiation treatment. The results were statistically analysed and showed that there was a correlation between the initial graded appearance of the nasal planum SCC and the period of survival. There was no statistically significant effect on survival of the independent variables of age, sex, and total radiation dose. However the clinical evidence was, that cats presenting with early nasal planum SCCs and treated with a low dose of radiation survived well. Those with more advanced lesions responded less favourably but enjoyed the palliation of pain that the radiation provided. This study has shown that mega-voltage radiation can play a most effective part in the treatment of actinic induced nasal planum squamous cell carcinoma. The challenge is to educate the owners and veterinarians to recognise the condition at an early stage and for veterinarians to have access to mega voltage radiation machines.